How Does the Human Capital, as an Engine of Growth, remain Untapped in Developing Countries Like Pakistan? - Dr. Abdul Hamid; Akram, Naeem (Dialogue Social Science Review (DSSR), 2025)
The growth and Development of both developed and underdeveloped economies depends upon the optimal exploitation of physical and human resources combined with the technology. Whereas historical evidence depicts that developed countries have derived better and multifaceted outcomes from enhanced technical and technological productivity caused by their human capital, developing countries failed to harness and convert their abundant population into an engine of growth and productivity. Resultantly, it has dragged these economies into a ‘vicious circle’ of poverty and dependency along with socio-political and economic pandemonium.